An autonomous robot for waiter service in restaurants - Omair, Mohd. Abdullah; Rakib, Al Shahriar Hossain; Khan, Md. Amir; Mahmud, Rubaiyat Talat (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.